Apathy and the Integrity of the Electoral Process in Nigeria - Okolie, Aloysius-Michaels (University of Nigeria Journal of Political Economy, 2021)
The stupendous electoral fraud that was recorded .... is bound to produce negative consequences on the electorates. ’" it will lead to monumental political apathy. Eligible voters traumatized by the vicious and organized violence that left many people dead and several others injured and/or maimed are bound to recline from participating or voting in subsequent elections.